Onion and garlic adding wealthy flavour - Gopal, Jai; Gadge, S S (Indian Horticulture, 2019)
Onion and garlic are important vegetable commodities mostly used for culinary purpose. Besides, both have several medicinal values. During past 20 years, production of onion in India has increased more than four times and that of garlic more than two times. ICAR-DOGR has played an important role in this increase. Since, onion and garlic are potential commodities traded in domestic as well as foreign markets, both play a crucial role in the Indian economy. The Directorate of Onion and Garlic, at Pune, has done a tremendous job in development of varieties and technologies which are quite helpful in enhancement of net return of our farmers.